2017
DOI: 10.1039/c7cc06607d
|View full text |Cite
|
Sign up to set email alerts
|

From boron clusters to gold clusters: new label-free colorimetric sensors

Abstract: A fundamental boron cluster, [closo-BH], mainly known as an inert agent for boron neutron capture therapy, can also serve as a bi-functional reductant and a capping agent for the formation of monodispersed size-controlled gold nanoparticles (AuNPs) under mild reaction conditions. The obtained AuNPs remained thermo-dynamically stable over 3 months, and exhibited high performance in phase transfer and sensing of heavy metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Recently, we reported that Cs 2 [ closo ‐B 12 H 12 ], a fundamental boron cluster, can serve as a bifunctional reductant and capping agent for the fast formation of monodispersed size‐controlled Au NPs under mild reaction conditions. The preparation process only involved two additives: chloroauric acid and boron clusters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that Cs 2 [ closo ‐B 12 H 12 ], a fundamental boron cluster, can serve as a bifunctional reductant and capping agent for the fast formation of monodispersed size‐controlled Au NPs under mild reaction conditions. The preparation process only involved two additives: chloroauric acid and boron clusters.…”
Section: Resultsmentioning
confidence: 99%
“…These results implied the high efficiency of the boron clusters in the preparation of size‐controlled monodispersed Au NPs. Likewise, this size‐control strategy, in which boron clusters play a dual role (reductant and stabilizer), can also be applied to synthesize other metal NPs (Ag and Pt), which we have reported previously …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then in 2018, our group further revealed that the complex of boron clusters with macrocyclic cucurbiturils, also driven by chaotropic effect, could grow continuously to nanoscale supramolecular networks . More encouragingly, we found more virtues of boron cluster at the same year, such as its highly efficient reducing ability and stabilizing effect to noble metal NPs . Besides, the metal cations in boron cluster can be exchanged to organic ammonium cations, accompanied by its controllable solubility in water and oil solvents .…”
Section: Introductionmentioning
confidence: 88%
“…[38,39] More encouragingly, we found more virtues of boron cluster at the same year, such as its highly efficient reducing ability and stabilizing effect to noble metal NPs. [40] Besides, the metal cations in boron cluster can be exchanged to organic ammonium cations, accompanied by its controllable solubility in water and oil solvents. [41] As boron cluster has so many advantages, we anticipate utilizing its superchaotropic and reducing features to fabricate supramolecule-linked metal nanocomposites.…”
Section: Introductionmentioning
confidence: 99%